Optimal layout of a LPG storage facility to minimize risk to human: article - Mohd Yusof, Nur Radiah; Abdul Rashid, Zulkifli (2017)
Application of LPG is extensive in domestic and industrial use. Because of the wide range application of LPG, the quantity of LPG increases every year. Due to the characteristics of LPG that are flammable and explosive, the LPG need to be handle with safe. Storage facility plays an important roles in the industry especially petrochemical product and gaseous product. Storage facility functions are to accumulate industrial product. In chemical industry, all product contain hazardous material that can cause vast impact and disaster to human and environment since they are the sources of catastrophic accident like fire and explosion and they also can cause harm to human health when toxic release occur. The chemical plants facility layout usually have been set up and installed without considering the optimal siting based on minimum risk consequences value. This research aim to identify optimum location for a LPG storage facility in order to minimize the risk to human. Here, in this work, probit equations were applied to estimate damage produced by thermal radiation on human (for second degree burns and lethality). An analysis is then performed to evaluate the percentage of affected people in the LPG damage, results shows the optimal layout consists of low percentage of affected people.